Integrated geoelectrical resistivity and hydrogeochemical methods for delineating and mapping heavy metal zone in aquifer system - Islami, Nur; Taib, Samsudin; Yusoff, Ismail; Ghani, Azman Abd (Springer Verlag (Germany), 2018)
A novel study on using geoelectrical resistivity, soil property, and hydrogeochemical analysis methods for delineating and mapping of heavy metal in aquifer system is presented in this paper. A total of 47 surveys of geoelectrical resistivity with Wenner configuration were conducted to determine the subsurface and the groundwater characteristics. The groundwater sample from 53 existing wells and 2 new wells has been analyzed to derive their water chemical content. The chemical analysis was done on the soil sample obtained from new two wells and from selected locations. The water and soil chemical analysis results from the new two wells were used as calibration in resistivity interpretation. The occurrence of heavy metal in aquifer system was expected to detect using the geoelectrical resistivity survey for the whole study area. The result of groundwater analysis shows that the groundwater sample contains a relatively low concentration of Fe (< 0.3 mg/L) elongating from the south up to the middle region. While in the middle and the northwestern, Fe concentration is relatively high (around 12 mg/L). Chemical analysis of soil sample shows that in the lower resistivity zone (< 18 Ωm), Al and Fe concentrations are comparatively high with an average of 68,000 and 40,000 mg/kg, respectively. Starting from the middle to the northwestern zone, the resistivity value appears to be low. It is definitely caused by higher Al and Fe concentration within the soil, and it is supported also by lower total anion content in the groundwater. While the resistivity value of more than 40 Ωm in aquifers is obtained in the zone which Fe concentration is relatively lower in the soil but not present in the groundwater. Correlation Fe concentration in the soil and Fe concentration in the groundwater sample shows the trend of positively linear; however, the Al concentration in soil has no correlation with Al content in groundwater. Finally, the probability of high heavy metal zone in the aquifer system is easily delineated by the distribution of geoelectrical resistivity presented in depth slice shapes which extend from the Boundary Range Composite Batholith in the north to the northwest.